The Impact of Risk Management to Sharia Insurance Business in Indonesia Market - Reza Ronaldo; Yulmaulini Yulmaulini (Journal of Islamic Business and Economic Review, 2021)
The purpose of this article is to determine risk management which is more important for an sharia insurance company in Indonesia and how important Risk Management for the insurance industry. Risk Management is very important to all business activities. Implementing Risk Management means the company has analysed the risks and impacts of risks for business continuity in the future as well as how to reach the expected opportunities by taking into account all possible risks that arise and how to anticipate all the possibilities that will occur. By running Risk Management will make it easier for companies to make long-term plans so that the company can run and develop well. In this article also contains why risk management really needs to be implemented and how the process of carrying out good risk management and how to develop risk management is a necessity in insurance organization.